Stakeholders’ Perspectives on Pre-Exposure Prophylaxis Innovative Interventions Implemented During COVID-19 Among Adolescent Girls and Young Women in North-West Province of South Africa - Lerato Lucia Olifant; Edith Phalane; Hlengiwe Mhlophe; Refilwe Nancy Phaswana-Mafuya (COVID)
South Africa’s health system was affected by the various mitigation measures implemented to control the rapid spread of the COVID-19 pandemic. However, innovative interventions were introduced to ensure service continuity. This study sought to explore the perspectives of stakeholders regarding the pre-exposure prophylaxis (PrEP) innovative interventions implemented during the COVID-19 lockdown period among adolescent girls and young women (AGYW), as well as their successes and improvements. We selected and interviewed 12 PrEP stakeholders, including professional nurses, case managers, peer educators, and counselors from the TB HIV Care programme in the Dr. Kenneth Kaunda District, in the North-West Province. The qualitative questions explored (1) how PrEP services were disrupted during the lockdown period, (2) how the disruptions were managed, and (3) the challenges and successes of the innovative interventions implemented. The interviews were audio-taped, transcribed, and thematically analyzed through Tesch’s eight steps of analysis. The stakeholders confirmed that COVID-19 disruptions affected the provision of PrEP services in terms of recruitment, counseling, HIV testing, and adherence support offered in different community hotspots. Responding to these difficulties, alternative avenues such as social media platforms were implemented and used for service continuity. The themes that emerged were organized into the following two categories: PrEP services provided during and after the COVID-19 lockdown period, as well as the successes and challenges. The current study provides further insight into COVID-19, aiming to inform preparations for future pandemics. Innovative PrEP interventions alleviated COVID-19 disruptions in some settings and improved HIV services, but this was not the case in the selected study area.